Post-Docking Optimization and Analysis of Protein-Ligand Interactions of Estrogen Receptor Alpha using AMMOS Software - Pencheva, Tania; Jereva, Dessislava; A. Miteva, Maria; Pajeva, Ilza (Current Computer - Aided Drug Design, 2013)
Understanding protein-ligand interactions is a critical step in rational drug design/virtual ligand screening. In this work we applied the AMMOS_ProtLig software for post-docking optimization of estrogen receptor alpha complexes generated after virtual ligand screening protocol. Using MOE software we identified the ligand-receptor interactions in the optimized complexes at different levels of protein flexibility and compared them to the experimentally observed interactions. We analyzed in details the binding sites of three X-ray complexes of the same receptor and identified the key residues for the protein-ligand interactions. The complexes were further processed with AMMOS_ProtLig and the interactions in the predicted poses were compared to those observed in the X-ray structures. The effect of employing different levels of flexibility was analyzed. The results confirmed the AMMOS_ProtLig applicability as a helpful postdocking optimization tool for virtual ligand screening of estrogen receptors.
Keywords: estrogen receptor